1999
DOI: 10.1108/09696479910255701
|View full text |Cite
|
Sign up to set email alerts
|

Aiming for organisational learning: consultants as agents of change

Abstract: Suggests that interaction between managers and consultants may be a way for learning organisations to continue learning and developing. Looks at a study into the relationship between professional consultants and their clients to identify two leading factors in influencing whether organisational learning occurs. These imply that the consultant is central for the achievement of organisational development and success. Examines two specific cases and concludes that within this context, there are a number of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
1
21
0
3
Order By: Relevance
“…Further, the results of this study support the studies of Ulrich (1997), which state that organizational competitiveness will spring from organizational capabilities, such as speed, responsiveness, learning capacity and employee competence, and that the human resource department will be responsible for generating these capabilities. Further, the results support the research of Massey and Walker (1999) who found the role of consultants can influence organizational learning. London and Smither (1999) draw out the implications for human resource management practices within the organization by looking at the role of supervisors in creating a noncontrolling environment, which supports empowerment and self-development.…”
Section: Resultssupporting
confidence: 89%
“…Further, the results of this study support the studies of Ulrich (1997), which state that organizational competitiveness will spring from organizational capabilities, such as speed, responsiveness, learning capacity and employee competence, and that the human resource department will be responsible for generating these capabilities. Further, the results support the research of Massey and Walker (1999) who found the role of consultants can influence organizational learning. London and Smither (1999) draw out the implications for human resource management practices within the organization by looking at the role of supervisors in creating a noncontrolling environment, which supports empowerment and self-development.…”
Section: Resultssupporting
confidence: 89%
“…Schein focused his research the role that "consultation process" on plays on organisational development. Steele (1975) The learning process in consulting 'Learning is the essence of consulting' (Steele, 1975: 190) Walker and Massey (1999)…”
Section: Mckinley and Scherer (2000)mentioning
confidence: 99%
“…Various reasons have been proposed for the growth in the demand for professional consultancy services across the corporate, public and nonprofit sectors: consultants provide required expertise which management lack (Fincham 1999: 337 -9), consultants market "glossily packaged analytical techniques" to "ill-informed clients" (Williams 1972: 199), consultants act as agents of change (Massey and Walker 1999), or consultants legitimise (and often carry out) the unpopular policies of management (Lapsley and Oldfield 2001: 527). Underlying these conventional roles are themes of "control, expertise and legitimation (Sturdy 1997b: 513).…”
Section: Professional Consultantsmentioning
confidence: 99%
“…Attention to consulting in academic and professional journals focuses mostly on practical issues, including the desirability of gaining consulting work and how to market to that "niche" (Stivers andCampbell 1995, Burdett 1994), consultants as facilitators of "organizational learning" (Massey and Walker 1999), and the benefits of "systemic" consulting (Baitsch and Heideloff 1997). Other research has focused on reasons why organisations employ consultants (Sturdy 1997a), the nature of the consultant-client relationship (Fincham 1999), the "dispassionate" advice offered by consultants (Berry and Oatley 1994), and the benefits of board-level consultancies (Werther and Kerr 1995).…”
Section: Professional Consultantsmentioning
confidence: 99%